The truth about win-win negotiating - Thompson, Leigh L. (FTPress Delivers elements., 2011)
This Element is an excerpt from The Truth About Negotiations (9780136007364) by Leigh Thompson. Available in print and digital formats. What "win-win" negotiation really means--and how to put it to work for you Seasoned negotiators will tell you the only good negotiation is one that ends in a win-win. Yet some people think that simply means reaching any agreement. Others think it's a negotiation that leaves all parties still speaking. Still others think it means dividing everything equally down the middle. Although all these outcomes are desirable, none captures the central concept of a win-win negotiation...